Karakterisasi Sensor Magnetik Fluxgate Berkonfigurasi 2 x (100/500/100) - Mukhlizar Mukhlizar; Mitra Djamal; Murhaban Murhaban (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2018)
Lack of measuring instruments with high resolution, still leaving a hindrance in terms of weak magnetic field measurement. One method that can be done to measure the magnetic field is fluxgate method. Fluxgate working range sensor to detect magnetic fields ranging from 10-10 - 10-4 T both DC and AC. Fluxgate sensor has high sensitivity, stable to high temperatures, low power operation, small size, and resolution up to 10 pT. So the fluxgate sensor is suitable for measuring weak magnetic fields. Has performed characterization of magnetic sensors fluxgate configuration with 2 × (100/500/100). The sensitivity obtained at 1.8 V/μT and sensor resolution of 0.56 nT/mV. Absolute error obtained sensor maximum of 0.0334 μT with a relative error of 0.85%.  Keywords: Fluxgate, sensitivity, resolution, a weak magnetic field